Sex- and genotype-dependent nicotine plus cue-primed reinstatement is enhanced in adolescent Sprague Dawley rats containing the human CHRNA6 3′-UTR polymorphism (rs2304297) - Carreño, Diana; Lotfipour, Shahrdad (Frontiers in Psychiatry, 2023)
Rationale: Large-scale human candidate gene studies have indicated that a genetic variant (rs2304297) in the alpha(α)6 nicotinic acetylcholine receptor (nAChR) subunit, encoded by the CHRNA6 gene, may play a key role in adolescent nicotine addictive behavior. We hypothesized that the polymorphism selectively enhances nicotine + cue-primed reinstatement, but not nicotine- or cue- reinstatement in α6GG (risk) versus α6CC (non-risk) allele carriers, without having baseline effects on natural rewards. Methods: Using CRISPR-Cas9 genomic engineering, we developed a humanized rat line with the human gene variant of the CHRNA6 3’-UTRC123G polymorphism in Sprague-Dawley rats. Genetically modified adolescent male and female rats were food trained under a fixed-ratio (FR)1 schedule of reinforcement and progressively increased to FR5. Animals were implanted with catheters and began nicotine self-administration (15 μg/kg/infusion) at FR5. Upon reaching stable responding, reinforced behavior was extinguished by removal of drug and cues. Reinstatement testing began for cue only, nicotine only, and nicotine + cue in a Latin Square Design. Animals were returned to extinction conditions for 2 days minimum between testing. Results: For natural food rewards, nicotine self-administration, progressive ratio, and extinction, adolescent male and female (α6GG and α6CC) rats exhibited equivalent behaviors. Male α6GG rats show enhanced nicotine + cue-primed reinstatement when compared with male α6CC rats. This genotype effect on reinstatement was not seen in female rats. Conclusions: Our findings support the in vivo functional role of the human CHRNA6 3’-UTR SNP genetic variant in sex-dependently enhancing nicotine seeking behavior in adolescent rats. Overall, the findings support clinical and preclinical data highlighting a role of α6 nAChRs mediating sex heterogeneity in substance use and related phenotypes.